Aspects of freedom in Mesopotamia - Huseen, Yasir Hashim (Al-Adab Journal, 2015)
The research focused on studying some aspects of freedom in Mesopotamia, and gave us an idea about the ancient Iraqis ability to explain their point of view in different manner of expressions and their opinions about the rulers and kings policies that got the benefit and welfare to them. This gives an evidence of course scope that was achieved by the ancient Iraqis society in the thought range at that time. Henceforth, The religious freedom had occupied an important space in Mesopotamian society since the worship practice and ritual performance were the most important matters to the people. However, the belief selection of ancient Iraqis were pulling out from their